Coronial findings pertaining to non‐opioid and non‐benzodiazepine drug‐related deaths in Australia. (30th May 2019) - Phillips, Helen; Naunton, Mark; Jackson, Shane L.; Kosari, Sam; Peterson, Gregory M.
Abstract: Using Australian coroners' inquest findings, this study investigated characteristics of non‐opioid and non‐benzodiazepine accidental drug‐related deaths, and coroners' recommendations applicable to pharmacists. A retrospective thematic analysis was conducted of narrative text from coronial findings of non‐opioid and non‐benzodiazepine drug‐related deaths ( n = 33; 18 males, 15 females; mean (±SD) age 50.3 ± 19.3 and 57.7 ± 22.0 years, respectively) published on the Internet between January 2012 and October 2017. A wide range of drugs was implicated in drug‐related deaths, with drugs relating to mental health conditions (antidepressants, antipsychotics) found to be the most prevalent and increasing over the 5‐year period. A history of mental health illness was common. Coroners' comments pertaining to pharmacists were limited to the requirement to maintain accurate records. A greater appreciation of the role of pharmacists is required by coroners, with many of the coroners' recommendations directed to other health professionals relevant to the pharmacists' role of promoting the safe use of medicines.